THE ANALYSIS OF CHEMISTRY BOOK’S EFFECTIVENESS IN LEARNING PROCESS - Siska Oktapianti (CV. Lafadz Jaya, 2026)
A book is useful to train students to learn independently which are systematically arranged to achieve learning objectives. Learning using modules will make learning more effective, efficient and relevant. The purpose of this research is to specify the effectiveness of the book : Atomic Structure and Chemical Element. This is a field research by using pretest - posttest control group design. The sample is 11 Chemistry Education students for the Chemistry Class, Odd Semester 2023/2024 chosed to assure a deputy cohort. Interview, documentation, and test questions are carried out to get the data by using the N-Gain test. The grade of students is 0.5 in the moderate category. It explains that the book can upgrade students' knowledge and understanding. Learning with the developed book can make students more viable in the class and has been potent in upgrading student learning achievements. Therefore, it is recommended that lecturers in the field of Chemistry Studies can use this book and can develop it for other discussion topics.